Life and creative activity under the stranger name: about some results of researches of biography of Yu.V. Kondratyuk ( O.G. Shargei) - I. O. Pistolenko (History of science and technology, 2015)
Оne of the scantily explored the historians of science and  technique facts of a change to them of the name and last name of  scientist in the field of theory of space flight Yuri Kondratyuk’s biography  (real name Olexandr  Shargei) is  examined in the article on the basis of analysis of the archived sources and row of publications.